ANALYZING THE ETHNO-ESD MODULE DEVELOPMENT FOR CRITICAL THINKING IN ELEMENTARY STUDENTS - Gina Tuty Alawiyah; Ghullam Hamdu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This research was motivated by the gap between the demands for strengthening critical thinking and sustainability principles and the practice of science education in elementary schools, which has not been systematically integrated with local culture. Although the potential of ethnoscience and Education for Sustainable Development (ESD) values is considerable, learning modules that explicitly combine local culture, sustainability, and critical thinking indicators in a coherent pedagogical framework are still limited. This study aims to analyze the development of an Ethno-ESD module as a basis for designing teaching tools that support the strengthening of critical thinking in elementary school students. The research uses a qualitative approach with a needs analysis design through observation, interviews, and documentation studies. The data sources come from teachers and fourth-grade students at SDN 4 Sumelap and science learning tool documents. The results show that the integration of local cultural values and ESD in learning is still implicit and not yet structured in terms of objectives, activities, and assessments, so that critical thinking indicators have not developed optimally. This study recommends the development of an Ethno-ESD module that is systematically designed to include the context of local ethnoscience, the explicit integration of sustainability values, and activities and assessments based on critical thinking indicators. This study has an impact on strengthening science learning design that is more contextual, reflective, and sustainability-oriented, as well as providing a conceptual contribution to the integration of ethnoscience, ESD, and critical thinking development at the elementary school level.